PHYSICAL, MECHANICAL AND CHEMICAL PROPERTIES OF PLUMS (cv. Santa Rosa) AFFECTED BY AMINOETHOXYVINYLGLYCINE APPLICATIONS - Altuntas, Ebubekir; Yaldiz, Mehmet (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The engineering properties (physical, mechanical and chemical) are importance to post harvest technologies of the agricultural materials. To plum fruits quality, the harvest and postharvest applications, the engineering properties of plum fruits should be considered. The effect of AVG (Aminoethoxyvinylglycine) treatments on some physical, mechanical and chemical properties of plum fruits (cv. Santa Rosa) were determined. Materials and Methods: For this research, the plant material ‘Santa Rosa’ plum (Prunus domestica) fruits were obtained in Tokat/Turkey (39o51' N and 40o55' E), in 2012. AVG treatments were as 0 mg L-1, 100 mg L-1 and 200 mg L-1, and three different harvest dates including 25 July, 1 August and 7 August were used. Results: The geometric mean diameter, volume of fruit and surface area values increased with AVG doses, whereas, fruit density decreased as AVG doses increased. L* and b* values decreased from 43.75 to 24.14 and 20.24 to 13.21, whereas, a* value increased from -9.03 to -2.63 for flesh plum, respectively. The fruit removal force of plum fruit increased from 19.09 N to 20.20 N in magnitude with an increase in AVG doses. The friction coefficients of fruits increased as AVG doses increased and harvest dates. Total soluble solids content was higher in AVG-0 (0 mg L-1) as compared to AVG-1 and AVG-2 (100 mg L-1 and 200 mg L-1) AVG-2 applications, whereas, pH and titratable acidity were lower in 200 mg L-1 as compared to 0 mg L-1 and 100 mg L-1 treatments. Post-harvest technological applications of the plum fruits must be designed by taking criteria into consideration for plum engineering properties.